Organizational Change in the Public Sector: A Bibliometric Analysis of Trends and Future Directions - Prasetyo, Febrianto Dwi; Heru Susilo; Ika Ruhana (Wacana Journal of Social and Humanity Studies, 2025)
In the unpredictable, uncertain, complex, and ambiguous (VUCA) terrain, where institutions must enhance effectiveness, transparency, and agility while navigating regulatory complexity and stakeholder resistance, organizational change has become increasingly significant in the public sector. The exploration of this content remains fragmented and lacks coherent quantitative approaches, despite a considerable amount of study. By tracing the development of exploration, relating to recreating themes, and identifying gaps to suggest an emerging exploration agenda, this study aims to clarify organizational change in the public sector. The study adhered to PRISMA guidelines to conduct a systematic literature review and bibliometric analysis, utilizing data from the Scopus database. We examined 169 peer-reviewed papers from 2000 to 2025 using VOSviewer and Bibliometrix to assess author networks, publishing trends, citation performance, and keyword co-occurrence. With the United States, Australia, and the United Kingdom being the main contributors and capitals of transnational cooperation, the results show a steady rise in publications since 2006. While prominent studies highlight the significance of regulatory reform, transformational leadership, and operational efficiency, keyword analysis reveals that organizational culture, leadership, communication, and adaptation are critical facilitators of change. The position of transnational collaboration and multidisciplinary involvement in exploration performance is moderate, yet failings persist in addressing non-Western settings and incorporating diverse theoretical frameworks. This exploration advances the theoretical understanding of adaptation in public sector reform, utilizing bibliometric mapping in conjunction with a methodical review methodology, and offers valuable insights for interpreters and policymakers on how to manage organizational change. Cross-regional, multilingual, and multidisciplinary approaches should be the focus of future exploration to support more inclusive and contextually relevant outcomes in public sector transformation.   Keywords: Bibliometric Analysis; Biblioshiny; Organizational Change; Public Sector; VOSviewer